Child mortality after the Ebola virus disease outbreak across Guinea, Liberia, and Sierra Leone - Eun Kim, Young (Elsevier, 2022)
The Ebola virus disease outbreak in 2014-2016 had a substantial impact on population health in Guinea, Liberia, and Sierra Leone. This study aimed to assess whether the impact continued after the outbreak ended regarding child mortality. Cross-sectional logistic regressions were run using data from the Demographic and Health Surveys in the three countries. The average child mortality rate was significantly lower for children born after the outbreak than for those born before. However, the association of the child mortality rate with an increase in the number of Ebola cases per 100,000 people was significantly stronger for children born after the outbreak ended. Also, the change in the utilization of maternal health services after the outbreak varied across health services. Restoring disrupted child health services to pre-Ebola levels may be more difficult in areas that suffered a higher number of Ebola cases. The recovery of maternal health services after the outbreak might be affected by factors such as the resilience of health systems at the subnational level. This study suggests that strengthening the health system is crucial to fully recover from the Ebola outbreak and cope with future epidemics.